Large‐Scale Transdisciplinary Collaboration for Adaptation Research: Challenges and Insights. Issue 4 (2nd May 2018) - Cundill, Georgina; Harvey, Blane; Tebboth, Mark; Cochrane, Logan; Currie‐Alder, Bruce; Vincent, Katharine; Lawn, Jon; Nicholls, Robert. J.; Scodanibbio, Lucia; Prakash, Anjal; New, Mark; Wester, Philippus; et al.
Abstract: An increasing number of research programs seek to support adaptation to climate change through the engagement of large‐scale transdisciplinary networks that span countries and continents. While transdisciplinary research processes have been a topic of reflection, practice, and refinement for some time, these trends now mean that the global change research community needs to reflect and learn how to pursue collaborative research on a large scale. This paper shares insights from a seven‐year climate change adaptation research program that supports collaboration between more than 450 researchers and practitioners across four consortia and 17 countries. The experience confirms the importance of attention to careful design for transdisciplinary collaboration, but also highlights that this alone is not enough. The success of well‐designed transdisciplinary research processes is also strongly influenced by relational and systemic features of collaborative relationships. Relational features include interpersonal trust, mutual respect, and leadership styles, while systemic features include legal partnership agreements, power asymmetries between partners, and institutional values and cultures. In the new arena of large‐scale collaborative science efforts, enablers of transdisciplinary collaboration include dedicated project coordinators, leaders at multiple levels, and the availability of small amounts of flexible funds to enable nimble responses to opportunities and unexpected collaborations. Abstract : Large‐scale transdisciplinary collaborations are becoming increasingly common in global change research. In these collaborative contexts, relational issues such as trust, respect, and leadership are critical. Systemic issues such as partnership agreements, power differences, and institutional values and cultures deeply influence outcomes. Key enablers of success include dedicated project coordinators and flexible funds to enable responses to opportunities.